Early winter avifaunal diversity from Buxa Tiger Reserve and Rasikbeel Wetland Complex of northern part of West Bengal, India - Adhurya, Sagar; Banerjee, Moitreyee; Pal, Achintya Kumar; Roy, Utpal Singha (Our Nature, 2017)
The present study was carried out to record the avifaunal diversity and abundance in and around Buxa Tiger Reserve (Raja Bhat Khawa, Buxa Fort, Raimatang and Jayanti) and Rasikbeel Wetland Complex, situated at the northern part of West Bengal, India during 19th – 22nd November, 2013. A total of 60 bird species belonging to 31 families were identified during four days of study period of which 8 were winter migrants, one was summer migrant and rest were resident. Anthropogenic interventions have altered much of the natural habitat of the present study location; however, a healthy avifaunal diversity was recorded during the present study. More intensive investigations will certainly enrich our knowledge of avian diversity and distribution pattern from the present study location leading to the proper conservation of this important bird area. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.